2013
DOI: 10.1159/000353779
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exposure to a Novel Female on Symptoms of Infection and on the Reproductive Axis

Abstract: Background/Aim: Sickness behaviors are the behavioral alterations animals exhibit during the course of an infection, often accompanied by reduced reproductive activity. Adopting sickness behaviors may aid in overcoming the infection, by diverting energy from routine activities towards enhancement of the immune system. Nonetheless, sickness behaviors are plastic, being influenced by specific environmental and social circumstances. Here, we tested whether the presentation of a novel female to males suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
(86 reference statements)
4
23
0
Order By: Relevance
“…We found that an inflammatory stimulus, such as LPS, can cause a significant decrease in song rate, in accordance with previous results obtained in other species Munoz et al 2010;Lopes et al 2013). Since the activation of the immunoresponse is expensive (see BIntroduction^), a negative relationship between the expression of a demanding trait, such as birdsong, and an inflammatory response was expected (Hasselquist and Nilsson 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that an inflammatory stimulus, such as LPS, can cause a significant decrease in song rate, in accordance with previous results obtained in other species Munoz et al 2010;Lopes et al 2013). Since the activation of the immunoresponse is expensive (see BIntroduction^), a negative relationship between the expression of a demanding trait, such as birdsong, and an inflammatory response was expected (Hasselquist and Nilsson 2012).…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that the mitigated sickness syndrome mirrored the suppression of the immune response expressed at the physiological level and that starlings fed with extra carotenoids could have switched from a costly inflammatory response to a highly specific, but less costly, antibody production (Lee 2006), accelerating the recovery processes. Nevertheless, another scenario is also possible as the behavioural symptoms of sickness induced by LPS can be suppressed without altering the inflammatory response (Lopes et al 2013). Indeed, Lopes and colleagues detected the presence of specific inflammatory interleukins both when birds displayed sickness behaviour and when they did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the benefit of “hiding” a sickness response from a potential mate outweighs the costs of losing the opportunity to mate, then one would predict social modulation of sickness behavior (Avistur and Yirmiya, 1999; Lopes, 2014). Indeed, male zebra finch ( Taeniopygia guttata ) injected with LPS and exposed to a novel female mask sickness behavior; they exhibit courting behaviors and activation of the HPG axis similar to control-injected males (Lopes et al, 2013). In rats, IL-1 injection suppresses mating behavior in female but not males rats, even though both sexes display a decrease in activity (Yirmiya et al, 1995).…”
Section: Acute Phase Response and Sickness Behaviormentioning
confidence: 99%
“…There is also indication that immune challenged male zebra finches (Taeniopygia guttata) are affected by the presence of a potent sexual stimulus. When presented with a novel female, animals suffering from a simulated acute infection were able to not only behave similarly to controlinjected birds, but also to activate their reproductive axis and to court females to the same extent as the controls [35]. However, experiments in male mice show an almost opposite effect, with an increase in depressive-like behaviours when presented with a receptive female, as compared to control males kept in isolation, as well as elimination of mating behaviour, as compared to control-injected mice [36].…”
Section: (A) Matingmentioning
confidence: 99%